A peregrinação a Meca em tempos de Cruzadas: o testemunho de Ibn Jubayr (século XII) - Milhomem, Thiago Damasceno Pinto (2018)
Pilgrimage to the holy city of Mecca (ḥajj) has been one of the pillars of Islam since the seventh century, the time of the advent of the religion in the Arabian Peninsula, as an ordering in the Holy Qur'an and in the sayings and deeds of Prophet Muḥammad. Being this pilgrimage mandatory for all faithful adults in good enough physical and material conditions, different personalities of the Islamic world have realized the sacred journey in different times. Many have left their written testimonies, as a legacy of their observations and impressions on societies and historical events of Islamic and non-Islamic domains, thus influencing the emergence of a specific literary genre of Arab-Islamic culture, the travel journal (rihla). One of the pioneers of this genre was Ibn Jubayr (1145-1217), a Muslim from the city of Valencia, writer of a journal of his travels to the region that today corresponds to the Middle East, between 1183 and 1185, a period between the Second and the Third Crusade. We use Ibn Jubayr's travel journal edited as “Through the East (Rihla)”, a version published by Alianza Literaria in 2007, and which consists of a translation from Arabic into Spanish by Felipe Maíllo Salgado. From this testimony, centered on the religious journey of the writer-traveler to Mecca, we analyze the possibilities and social conditions of ḥajj at the end of the twelfth century, in the context of the Crusades, a long-lasting historical phenomenon permeated by important religious, political, economic, military and cultural aspects